Effectivity of Digital Information Systems in improving the productions of Palm Oil Plantation using Six Sigma DMAIC (Case study in PT. Alam Plantase Indah) - Aria Setyoko; Tukhas Shilul Imaroh (Budapest International Research and Critics University, 2022)
Palm oil and its processed products is one of the highest foreign trades in Indonesia. PT. Alam Plantase Indah is one of the palm oil plantations in Indonesia that has high operational challenges, where issues of labor, land, market prices, and production quality are the starting point for the quality of processed products into CPO and other derivative products. However, judging from the productivity of palm oil plantations in Indonesia, it is still inferior to several neighboring countries whose productivity is higher than the national average productivity. From preliminary observation in July 2021 PT. Alam Plantase Indah has Capability Process (CP) value is 77 and sigma score is 2.67 σ. This study aims to measure the effectiveness of the using plantation digitalization system to increase crop productivity in palm oil plantations using DMAIC Six Sigma approach in order to find out the root cause of the problems whether the digitalization model applied is able to solve these problems so that it can participate in increasing the productivity of plantations that apply the system of digitalization.